EVALUASI KONSEPTUAL ATAS PSAK NO. 26 SERTA DAMPAKNYA TERHADAP SEKTOR PROPERTI - Wirjolukito, Aruna (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
Implementation of capitalization treatment of borrowing costs is often questioned related to the effective of accounting information presentation. So far, PSAK Indonesia had already adapted these issues taken from SFAS. About two half years later, PSAK No. 26 had been revised at mid term of January 1997, by adding some important stressing about qualifying assets. One thing to be considered in accounting treatment implementation is the false impact in the process of decision making, e.g. in [1] investment decision and [2] bias effect related to the qualitative characteristics elements like relevance and reliability. Also, capitalization tends to leave conservatism principle behind. Related to the evaluation of interest cost capitalization effect that is implemented in property sector, PSAK No. 26 do not rule strictly about which procedures to be taken. So that, every company is free to [1] use capitalized interest cost valuation calculation method needed, [2] determine the period of interest cost capitalization, [3] record interest capitalization in certain asset account, and [4] not disclose transparently, mainly requirements beyond regulations. All that things can cause presented financial report containing not only bias, but also mark-up practice in assets value, earnings management, and presentation other numbers, which tend to be over-optimistic behavior. The less strict and fair regulations also bring lending institutions in dilemma situation, because companies often hide behind the chink of such regulations. PSAK No. 26 do not support users of financial report to more understand about core business of company (especially in property sector), on the other hand it gives many chances for companies to do many malpractices.